2016
DOI: 10.1084/jem.20160579
|View full text |Cite
|
Sign up to set email alerts
|

The scaffolding function of the RLTPR protein explains its essential role for CD28 co-stimulation in mouse and human T cells

Abstract: In two complementary papers, Casanova, Malissen, and collaborators report the discovery of human RLTPR deficiency, the first primary immunodeficiency of the human CD28 pathway in T cells. Together, the two studies elucidate the largely (but not completely) overlapping roles of RLTPR in CD28 signaling in T and B cells of humans and mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(111 citation statements)
references
References 55 publications
4
107
0
Order By: Relevance
“…It will be intriguing to know of CD28‐dependent glucokinase expression also regulates Treg cell migration to tumours. CD28 is also a major activator of the nuclear factor‐ κ B pathway, which may be more central to its co‐stimulatory function …”
Section: Pi3kδ Downstream Of Core T‐cell Receptorsmentioning
confidence: 99%
“…It will be intriguing to know of CD28‐dependent glucokinase expression also regulates Treg cell migration to tumours. CD28 is also a major activator of the nuclear factor‐ κ B pathway, which may be more central to its co‐stimulatory function …”
Section: Pi3kδ Downstream Of Core T‐cell Receptorsmentioning
confidence: 99%
“…When CD28 signalling is blocked at the time of T‐cell priming, T‐cell activation is suppressed and this prevents Tfh cell differentiation in vivo . CD28 co‐stimulation depends upon the RLTPR, a scaffold protein that links CD28 to the CARD11/CARMA1 cytosolic adapter and to the nuclear factor‐ κ B (NF‐ κ B) pathway . Mice and humans deficient in RLTPR have very few Tfh cells and this is associated with defects in activation‐induced expression of CD40L, ICOS and RelA phosphorylation (indicative of impaired NF‐ κ B signalling) .…”
Section: The Importance Of Co‐receptor Signals In Tfh Cell Differentimentioning
confidence: 99%
“…50,51 Mice and humans deficient in RLTPR have very few Tfh cells and this is associated with defects in activation-induced expression of CD40L, ICOS and RelA phosphorylation (indicative of impaired NF-jB signalling). 50,51 Once T cells have acquired CXCR5 expression and migrated to Bcell follicles the role of CD28 is less clear. Tfh cell differentiation can occur when CD28 co-stimulation is inhibited after priming in vivo by administration of CTLA-4immunoglobulin, a treatment that would also prevent CTLA-4 signalling.…”
Section: Presentation Of Antigen By B Cellsmentioning
confidence: 99%
“…They developed mice that bear a genetic tag allowing for AP-MS analysis of the RLTPR interactome in primary T cells, showed that RLTPR acts as a scaffold, bridging CD28 to the CARD11/CARMA1 cytosolic adaptor and to the NF-κB signaling pathway, and identified previously unknown proteins in the CD28 signaling pathway [100].…”
Section: Cluster Of Differentiation 28 (Cd28) Is a Protein Expressed mentioning
confidence: 99%